Sex differences in cardiologic medication provision for adults with coronary heart disease: an analysis of health claims data from 2018 to 2020 in Saxony-Anhalt, Germany - Fleischer, Steffen; Heinrich, Stephanie; Meyer, Gabriele; Mikolajczyk, Rafael; Lückmann, Sara Lena (BMC health services research, 2024)
Background Coronary heart diseases (CHDs) have experienced the largest increase worldwide as a cause of death, accounting for 16% of all deaths. In Saxony-Anhalt, a federal state in Germany, both CHD morbidity and acute myocardial infarction mortality rates are particularly high. Several risk factors associated with CHDs have been studied in Saxony-Anhalt, but sex differences in service use and medication have not been investigated. This study therefore aimed to investigate sex differences in the quality and quantity of cardiological care provided to adults with CHD. Methods This study used health claims data from 2018 to 2020 to analyse the utilisation of healthcare services and adherence to medication-related guideline recommendations in primary and specialist care. The sample included 133,661 individuals with CHD from a major statutory health insurance company (Germany). Results Almost all CHD patients (> 99%) received continuous primary care. Continuous cardiologist utilisation was lower for females than for males, with 15.0% and 22.2%, respectively, and sporadic utilisation showed greater differences, with 33.5% of females and 43.4% of males seeking sporadic cardiologist consultations. Additionally, 43.1% of the identified CHD patients participated in disease management programmes (DMPs). The study also examined the impact of DMP participation and cardiologist care on medication uptake and revealed that sex differences in medication uptake, except for statin use, were mitigated by these factors. Statins were prescribed to 42.9% of the CHD patients eligible for statin prescription in accordance with the QiSA indicator for statin prescription eligibility. However, there were significant sex differences in statin utilisation. Female CHD patients were less likely to use statins (35.2%) than male CHD patients were (50.1%). The difference in statin utilisation persisted after adjustment for DMP participation and cardiologist consultation. Conclusions This study highlights sex differences in the utilisation of cardiological healthcare services for patients with CHD in the Saxony-Anhalt cohort. These findings underscore the continuing need for interventions to reduce sex inequalities in accessing healthcare and providing health care for patients with CHD. Factors at the health care system, patient, and physician levels should be further investigated to eventually improve statin prescription in people with CHD, especially women.